The Effect of Blood Groups and Nutritional Habits of Different Classifications of Referees on the Success of Turkish Football Management - Mendes, Bekir; Bingolbali, Abdullah; Sengul, Mehmet (Researchtrentz Acad Publ Education Services, 2022)
Volunteer 247 football referees in the Turkish Professional Football Leagues were included in this study which aims to evaluate the effect of blood groups and nutritional habits of different classifications' referees on the success of Turkish football management. After the demographic information (age, height, weight, education level and blood groups (based on their statements)) of the referees were taken, the total refereeing times, their classifications and their duration in their classifications, and their nutritional information habits were obtained with a questionnaire. Classification Trees Method was used to determine the factors affecting the success (classification) of the referees. The distribution of the blood groups of the referees did not differ significantly from the distribution of the general blood groups in our country. However, A RH + and 0 RH + blood groups were seen more frequently in the study group. It was determined that 86.7% of the referees with a service period of more than three years, whose blood groups were 0 Rh+ or 0 Rh-, were top classification assistant referees. In our study, it was determined that the classification and classification assistant referees did not acquire regular eating habits and observed that the level of nutrition knowledge increased with a rise toward the top classification. It can be said that these results indicate the need for nutrition education for football referees. Among the referees with a two-year period, 73.8% of those who skip meals and say I have no appetite/habit are working as classification referees, and 72.2% of those who say to lose weight working as assistant referees. 50% of those who eat 2 or 5 meals a day are classification assistant referees, and 66.7% of those who eat 3 or 6 meals a day are classification referees. It was seen that 66.6% of the three-year referees who were fed with meat meal, salad, dessert or pasta before the competition were classification and classification assistant referees, and 73.5% of those who were fed with food groups such as vegetable food, yoghurt, fruit, boiled meat or chicken, meat, meatballs, rice, compote were top classification assistant referees.
Keywords: Success; Nutritional Habit; Football Referee; Blood Group; Football Management